Editors' Choice—Understanding the Superior Cycling Performance of Si Anode in Highly Concentrated Phosphonium-Based Ionic Liquid Electrolyte. Issue 12 (17th August 2020) - Araño, Khryslyn; Mazouzi, Driss; Kerr, Robert; Lestriez, Bernard; Le Bideau, Jean; Howlett, Patrick C.; Dupré, Nicolas; Forsyth, Maria; Guyomard, Dominique
Abstract : Considerable effort has been devoted to improving the cyclability of silicon (Si) negative electrodes for lithium-ion batteries because it is a promising high specific capacity alternative to graphite. In this work, the electrochemical behaviour of Si in two ionic liquid (IL) electrolytes, triethyl(methyl)phosphonium bis(fluorosulfonyl)imide (P1222 FSI) and N -propyl- N -methylpyrrolidinium-FSI (C3 mpyrFSI) with high and low lithium (Li) salt content is investigated at 50 °C. Results highlight that higher capacity and better cycling stability are achieved over 50 cycles with high salt concentration, the first time for a pyrrolidinium-based electrolyte in the area of Si negative electrodes. However, the Si cycling performance was far superior in the P1222 FSI-based high salt content electrolyte compared to that of the C3 mpyrFSI. To understand this unexpected result, diffusivity measurements of the IL-based electrolytes were performed using PFG-NMR, while their stability was probed using MAS-NMR and XPS after long-term cycling. A higher apparent transport number for Li ions in highly concentrated ILs, combined with a significantly lower extent of electrolyte degradation explains the superior cycle life of the highly concentrated phosphonium-based system. Si/concentrated P1222 FSI-LiFSI/lithium nickel cobalt aluminum oxide (NCA) full cells with more than 3 mAh cm −2 nominal capacity deliver a promising cycle life and good rate capability.